Developing Coffee Cherry Skin and Coffee Husk by Products as Sustainable Novel Food and Fuel - Irawan, Andik; McLellan, Benjamin C; Hastutik, Septi Dwi (P3M Politeknik Negeri Jember, 2024)
Coffee plantations can potentially support an integrated sustainable coffee production (SCP) system, particularly through the expanded utilization of by-products. Smallholders mostly manage coffee plantations in Indonesia. Coffee processing cannot avoid waste entirely. However, poor processing will increase waste. This research aims to utilize by-products (coffee skin) to create novel food (cascara) and potential fuel. The raw materials from Cherry skin (CS) and Husk skin (HS) are obtained from wet and dry coffee processes. This research conducts the process of sorting raw cascara and roasting it. TDS and pH are examined to measure the level of extraction, while a group of panelists assess the aroma, taste, and mouthfeel using a series of scaling points for justification. CS does not require sorting. However, HS is sorted into three sizes: 7.5mm, 6.5mm, and 5.5mm, respectively. In this study, 1,000g HS has an approximate size distribution of about 25% 7.5 mm, 15% 6.5 mm, and 20% 5.5 mm; the rest is dust and green beans (GB) coffee pixels. In conclusion, CS and HS were roasted to produce food products (cascara). About 2.5kg of raw HS is needed for 1kg feed HS (7.5mm and 6.5mm). HS measuring 5.5mm or below, and the remaining fraction of dust makes up about 54% of the raw feed and can be used as fuel (briquettes).